A cross-sectional survey interconnecting health information seeking behavior with clinical data of type 2 diabetes mellitus patients. Issue 2 (19th May 2020) - Kostagiolas, Petros; Tsiligros, Panagiotis; Theodorou, Panagiotis; Tentolouris, Nikolaos; Niakas, Dimitrios
Abstract : Purpose: The purpose of this paper is the investigation of type 2 diabetes patients' information seeking behavior in terms of their information needs, sources and barriers faced by patients when seeking information. The information seeking behavior is associated with clinical patient data. Design/methodology/approach: The relevant literature is reviewed, and the results of a cross-sectional survey informed by Wilson's macro-model of information seeking behavior are reported. The survey includes 106 outpatients from the diabetes clinic of a Greek major university hospital and includes information seeking behaviors and patient's clinical evidence. Findings: The most important health information needs are related to the complications, symptoms and causes of diabetes, to the proper diet for diabetics and the measures adopted to avoid foot complications. Furthermore, the most important information resources were physicians, ophthalmologists, books, broadcast media and family members. Obstacles encountered during information seeking include the complicated nature of health information, which involves scientific terms as well as psychological issues. The diabetes stage is correlated with information needs for diabetes medication, while the years from the first diagnosis are negatively correlated with the use of informal sources. Research limitations/implications: The information needs and sources of diabetic patients, as well as the main obstacles to this pursuit, could potentially have important implications in designing a future information campaign and information services for diabetes patients. Originality/value: The Wilson's macro-model of information seeking has been applied to the diabetic patients' information seeking behavior; while information needs, information sources and information obstacles are correlated with clinical evidence from patients' hospital records.